2017
DOI: 10.15562/gnc.60
|View full text |Cite
|
Sign up to set email alerts
|

Dental Tissue-Derived Stem Cells as a Candidate for Neural Regeneration

Abstract: In recent years, stem cell therapy tried to improve the life of patients that suffer from neurodegenerative disease, like Alzheimer's disease. Although teeth are non-essential for life, but the dental tissues are an important source of mesenchymal stem cells that are suitable for neural regeneration. The studies showed that dental stem cells (DSCs) have the potential to differentiate into several cell types that among the most important is neural progenitor. In this review article, discusses the types of denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…SCO is widely used as a model for studying therapeutic agents in AD therapy for induction of memory deficit in experimental animals. [ 30 ] In this study, we showed that SCO promoted memory impairment in the animals. The object recognition test results illustrated that SCO increases the latency to figure out a familiar object compared to a new object.…”
Section: Discussionmentioning
confidence: 73%
“…SCO is widely used as a model for studying therapeutic agents in AD therapy for induction of memory deficit in experimental animals. [ 30 ] In this study, we showed that SCO promoted memory impairment in the animals. The object recognition test results illustrated that SCO increases the latency to figure out a familiar object compared to a new object.…”
Section: Discussionmentioning
confidence: 73%
“…Dental-tissue-derived stem cells (DTDSCs) consist of six types of stem cells which can be isolated from the different anatomical locations on the dental tissues. However, it was shown that most of these DTDSCs lack a key feature of the MSCs which is multi-potency ( 7 ). Human MSCs pose a unique molecular fingerprint by expressing CD105, CD44, CD90, and CD73 but not CD79a, CD45, CD34, CD19, CD14, CD11b, and HLA-DR.…”
Section: Introductionmentioning
confidence: 99%